The combustion and emission improvements for diesel–biodiesel hybrid engines based on response surface methodology - Junming Li; Weihuang Zhong; Weihuang Zhong; Jian Zhang; Ziheng Zhao; Jingyi Hu; Jingyi Hu (Frontiers in Energy Research, 2023)
With the rapid technological progress of society and increasingly stringent environmental regulations, further reduction of emissions has become an important issue for environmental protection. This study developed a response surface model with the biodiesel blending ratio (BBR), load, and exhaust gas recirculation (EGR) as independent variables and brake thermal efficiency (BTE), brake specific fuel consumption (BSFC), and NOx, and CO emission rates as dependent variables. Simulations were performed and calculated. The results of the response surface approach with the objectives of maximizing the BTE of the engine and minimizing BSFC, NOx emissions, and CO emissions show that when the BBR is 20%, the EGR rate is 15%, and the engine load is 74.52%, pollutant emissions are significantly reduced while the engine power’s performance is maximized.